Determinación de costos a los procesos de Clínica CIROI CIA. LTDA; de la ciudad de Riobamba del período 2013 para establecer los precios de los servicios. - Contento Dias, Isabel Alexandra (2016)
This research is intended to study and the costs implementation, which are considered such important for planning, control, management and decision-making of the CIROI Clinic Cia. Ltda., of the Riobamba city during the period 2013. This study is composed of four chapters as follow: Chapter I, in this chapter, the research proposal, objectives, justification as well as the research process is stated. Chapter II contains the research theoretical framework which is divided into fourth units. Unit I presents the information on the research scope as well as the entity framework where this research was carried out, its constitution, mission, vision and its organizational structure. Unit II embraces the theoretical fundamentals of the Cost Accounting such as its definition, importance, the classification and treatment of cost production elements. In Unit III the cost and prices system is presented, and Unite IV makes reference to the contribution margin and the services offered Chapter III states the methodological framework where the research method techniques and instruments to be used are referred, and also the cost system evaluation is carried out through the analysis of results to determine the service cost. In Chapter IV, the study conclusions and recommendations are made from the research results and findings like the deviations in the determining of the costs of CIROI Cía. Ltda. Clinic services. And finally in Chapter V, the study proposal of determining the process cost of the Clinic CIROI Cia. Ltda., in the city of Riobamba the period 2013 to establish the prices of services is disclosed.